Prevalence of the polymorphic H-ficolin (FCN3) genes and mannosebinding lectin-associated serine protease-2 (MASP2) in indigenous populations from the Russian Arctic regions - M. V. Smolnikova; S. Yu. Tereshchenko (Вавиловский журнал генетики и селекции)
Lectins, being the main proteins of the lectin pathway activating the complement system, are encoded by polymorphic genes, wherein point mutations cause the protein conformation and expression to change, which turns out to have an effect on the functionality and ability to respond to the pathogen. In the current study, largescale data on the population genotype distribution of the genes for H-ficolin FCN3 rs28357092 and mannose-binding lectin-associated serine protease MASP2 rs72550870 among the indigenous peoples of the Russian Arctic regions (Nenets, Dolgans and Nganasans, a mixed population and Russians: a total sample was about 1000 newborns) have been obtained for the first time. Genotyping was carried out using RT-PCR. The frequency of the homozygous variant del/del FCN3 rs28357092 associated with the total absence of the most powerful activator of the lectin complement pathway, N-ficolin, was revealed; 0 % in the Nenets, 0.8 % in the Dolgans and Nganasans, and 3.5 % among the Russians ( p < 0.01). Analysis of the prevalence of the MASP2 genotypes has shown the predominance of the homozygous variant AA in all studied populations, which agrees with the available world data. The heterozygous genotype AG rs72550870 associated with a reduced level of protease was found to occur rarely in the Nenets, Dolgans and Nganasans compared to newborns of Caucasoid origin from Krasnoyarsk: 0.5 % versus 3.3 %, respectively. Moreover, among 323 examined Nenets, one AG carrier was identified, whereas in Russians, 16 out of 242 examined newborns were found to be AG carriers ( p < 0.001). A homozygous variant (GG) in total absence of protease with impaired binding of both MBL and ficolins was not detected in any of the 980 examined newborns. An additional analysis of infectious morbidity in Arctic populations allows one to find phenotypic characteristics related to a high functional activity of the lectin pathway of complement activation as an most important factor for the first-line of anti-infectious defense, including such new viral diseases as COVID-19.